Biocontrol agents in aquaculture: Production and their application - Munti Yuhana (Jurnal Akuakultur Indonesia)
The use of biocontrol agents have become commonly accepted as a 'natural weapon' in aquaculture, either as an ecological bioremediator for low environmental quality, as well as the health promoter for cultured organisms. Biocontrol agents, which consist of beneficial microorganisms, are commonly applied as biosupplements in feeds. They are potential in replacing the use of antibiotic in inhibiting the pathogenic organisms. Therefore, their application has revealed the potential as an effective strategy to reduce the over use of antibiotics in controlling the pathogenic agents, avoid the spreading the drug resistance, or environmental deterioration of the negative effect by killing useful microorganisms. The development of suitable technology for microbial agents production, viability and stability, is a key area of research for industrial production. Production of biocontrol agents should be based on the microbial criteria, and the ability to withstand stress during processing and storage of products is crucial. This review makes an overview of biocontrol agents selection studies including techniques for isolation/identification, selection, production and its application in order to be accepted as a valuable product in aquaculture.